Learning and using multiple languages current findings from research on multilingualism edited by Maria Pilar Safont Jordà and Laura Portolés Falomir. - Jordà, Maria Pilar Safont; Falomir, Laura Portolés (Cambridge Scholars Publishing, 2015)
This volume brings together the latest findings from research on multilingual language learning and use in multilingual communities. Suzanne Flynn, Hakan Ringbom and Larissa Aronin are some of the prestigious scholars who have contributed to this book.